Adaptive Optimizing Control for Nonlinear Synchronous Generator System with Uncertain Disturbance. (16th October 2019) - Deng, Guiyang; Cheng, Lianglun; Yang, Baojian
Abstract : In this paper, an adaptive optimizing control is proposed for nonlinear synchronous generator system with uncertain disturbance. Considering the issue of uncertain item, a low-order Extended State Observer (ESO) is constructed to track each order states. Then, combining Backstepping technology and proposed ESO, a dynamic compensation control is designed to compensate the uncertainty disturbance in each state quantity. The proposed method demonstrated that stability of the system can be ensured, and tracking burden of ESO can be reduced. Finally, simulation results can show a good tracking performance and anti-interference ability by the proposed control method.